1993
DOI: 10.1089/thy.1993.3.297
|View full text |Cite
|
Sign up to set email alerts
|

Detection of TSH Receptor RNA in Cultured Fibroblasts from Patients with Graves' Ophthalmopathy and Pretibial Dermopathy

Abstract: Fibroblasts are target cells for the autoimmune process in Graves' ophthalmopathy and pretibial dermopathy. Because the autoantigen involved in the hyperthyroidism of Graves' disease is the TSH receptor, we sought to determine whether RNA encoding this receptor might be present in retroocular and pretibial fibroblasts. RNA was reverse transcribed and the resulting cDNA was amplified by the polymerase chain reaction using primers spanning a region of the extracellular domain of the human TSH receptor. The predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
61
0
2

Year Published

1997
1997
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(67 citation statements)
references
References 17 publications
(20 reference statements)
4
61
0
2
Order By: Relevance
“…Since TSHR was first cloned in 1989, it has been believed to be responsible solely for the control of thyroid follicular cell growth and thyroid hormone synthesis (Nagayama et al 1989, Laugwitz et al 1996. However, it is becoming increasingly clear that expression of TSHR is not confined to the thyroid gland, but is widely expressed in a variety of tissues (Francis et al 1991, Endo et al 1993, Feliciello et al 1993, Heufelder et al 1993. TSHR protein expression has been reported in fibroblasts and adipose tissue from the retro-orbital space of Graves' patients, where it may play a role in thyroid-associated ophthalmopathy (Bahn et al 1998a,b, Starkey et al 2003, Bahn 2004.…”
Section: Discussionmentioning
confidence: 99%
“…Since TSHR was first cloned in 1989, it has been believed to be responsible solely for the control of thyroid follicular cell growth and thyroid hormone synthesis (Nagayama et al 1989, Laugwitz et al 1996. However, it is becoming increasingly clear that expression of TSHR is not confined to the thyroid gland, but is widely expressed in a variety of tissues (Francis et al 1991, Endo et al 1993, Feliciello et al 1993, Heufelder et al 1993. TSHR protein expression has been reported in fibroblasts and adipose tissue from the retro-orbital space of Graves' patients, where it may play a role in thyroid-associated ophthalmopathy (Bahn et al 1998a,b, Starkey et al 2003, Bahn 2004.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous results from several laboratories now suggest that the TSHr is expressed in various human extrathyroidal tissues (29,30,31). The presence of the TSHr in human orbital tissue and orbital fibroblasts was demonstrated by using RT-PCR in 1993 (8,9), but the possibility of an illegitimate transcription was raised (32,33,34). In a previous report, we demonstrated by using a very sensitive and quantitative method such as real-time PCR that the levels of TSHr mRNA expressed in orbital tissues from TAO patients were similar to those obtained from tissues of patients not affected by thyroid diseases (12).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there is no general agreement regarding the presence of the TSHr or its transcript in eye orbit structures. Some have found transcripts in retro-ocular fibroblasts (8) or inferred their presence in fat (9); others have failed to find a TSHr transcript in retro-ocular muscle also containing fibroblasts (10). A TSHr variant transcript comprising essentially exons 1 -8 was also described in many locations, including ocular muscle, fat, lymphocytes and fibroblasts (11).…”
Section: Introductionmentioning
confidence: 99%
“…Results of these studies were in general agreement and demonstrated the presence of TSHR mRNA and protein in orbital adipose tissue specimens and derivative cultures from patients with GO and from patients without GO. [13][14][15] However, additional studies showed that levels of TSHR are in fact higher in orbital adipose tissue from patients with GO than from patients without GO, suggesting that increased TSHR expression in the orbit might be involved in disease development. 16 This concept is further supported by the finding of a positive correlation between GO patients' TSHR mRNA levels in orbital adipose tissues excised during decompression surgery and the patients' clinical activity score.…”
mentioning
confidence: 99%